Legislative development and its impact on the digitisation in accounting practice in the Slovak Republic during the Covid-19 pandemic period - Mokošová, Daša; Blahušiaková, Miriama (Publishing House of Wroclaw University of Economics and Business, 2022)
MokoŠová, D., & BlahuŠiaková, M. (2022). Legislative development and its impact on the digitisation in accounting practice in the Slovak Republic during the Covid-19 pandemic period. In J. Dyczkowska (Ed.), Accounting and business in a sustainable post-Covid world: New perspectives and challenges (pp. 45-59). Wroclaw: Publishing House of Wroclaw University of Economics and Business.
s. 211
Keywords: rachunkowość; biznes; COVID-19; wyzwania; zrównoważony rozwój